INVESTIGATING THE IMPACT OF ENGLISH CAMP ACTIVITIES; THE STUDENT STUDY SERVICE’S PERSPECTIVE - Nuraeni .; Hida Kamila (EDUKHA, 2020)
In order to enhance the students’ outcomes in English learning, English campis one of teaching activities that integrates various skills of teaching techniques andincreases students’ learning outcome. The purpose of this study was to determine theimpact of English camp based on the perspective of the student study service. Themethods consisted of collecting data from five students study service, selected by random sampling with interviews, and data analysis by study casus. The findings reveal positive and negative impact of english camp activities